Freshwater ecosystem: A short review of threats and mitigations in Malaysia / Nur Amalina Mohd Izam ... [et al.] - Mohd Izam, Nur Amalina; Azman, Siti Nasuha; Jonit, Eliena; Sallehoddin, Siti Mastura Hanim; Khairul, Dinie Carmila; Zainul Abidin, Mohamad Kamaruddin; Farinordin, Farah Ayuni (Universiti Teknologi MARA Cawangan Pahang, 2021)
Freshwater ecosystem is an important ecosystem which provides humans and other organisms with basic necessities, such as water and food. However, due to increasing human population and demands, human exploitation has significantly changed the freshwater ecosystem, with changes affecting their physical, chemical, and biological characteristics. The freshwater ecosystem has been mismanaged for such a long time, leading to threats towards the ecosystem. In Malaysia, the emergence of harmful algal blooms, infectious disease, freshwater salinization, as well as climate change have threatened the freshwater ecosystem which consequently affect water quality and biodiversity surrounding the freshwater habitat. Increasing urban, industrial, and agricultural areas have significant effects on freshwater ecosystem, especially through soil leaching. Thus, mitigation steps are needed to reduce the effects of freshwater degradation, such as through education and awareness, research and monitoring, making polluters pay, and integrated holistic environmental management. These mitigations should be carried out by the responsible authorities, as well as all industries involved. Continuous monitoring involving technologies is recommended to monitor the current condition of freshwater ecosystem for further interventions.